Humidity-resistant perovskite solar cells via the incorporation of halogenated graphene particles. (August 2021) - Ibrahim, Khaled; Shahin, Ahmed; Jones, Alexander; Alshehri, Abdullah H.; Mistry, Kissan; Singh, Michael D.; Ye, Fan; Sanderson, Joseph; Yavuz, Mustafa; Musselman, Kevin P.
Graphical abstract: Highlights: Humidity-induced degradation remains a barrier to the commercialization of PSCs. Laser technique to produce halogenated graphene used to enhance PSCs stability. The laser-functionalization method is faster than previously reported methods. Limited degradation in ambient was observed over a 6000 hr testing span. Integration of halogenated particles enhanced the PV parameters. Abstract: One of the main challenges facing large-scale commercialization of perovskite solar cells (PSCs) is their stability and susceptibility to humidity. Herein, a rapid single-step laser treatment process is employed to fabricate highly hydrophobic, halogenated graphene particles. These particles are integrated into a planar cesium formamidinium lead iodide PSC architecture as an additive in the spiro-OMeTAD hole-transporting layer or as a capping layer on the spiro-OMeTAD. The graphene particles functionalized with chlorine and iodine were found to significantly enhance the stability of the PSCs in both ambient and highly humid conditions. Notably, inclusion of graphene particles functionalized with both iodine and chlorine resulted in the absorbance of an unencapsulated perovskite device decaying by only 18% over a 6000 hr testing span in ambient conditions. When the halogenated graphene particles were incorporated as an additive in the spiro-OMeTAD, the power conversion efficiency was also improved, which was attributed to improved hole extraction by the halogenated graphene particles, as observed by steady-state and time-resolved photoluminescence.